Knockdown of Zinc Transporter ZIP12 by shRNA Alters Genes Related to Mitochondria and Neuronal Differentiation in Neuro-2a Cells (P24-018-19). (13th June 2019) - Ojo, Babajide; Hart, Matt; Strong, Morgan D; Hwang, Hong; Hoyt, Peter; Bettaieb, Ahmed; Clarke, Stephen; Smith, Brenda; Lin, Dingbo; Lucas, Edralin A; Chowanadisai, Winyoo
Abstract: Objectives: Zinc is vital for brain function and preservation of cognitive potential in aging. However, mechanisms by which the nervous system regulates zinc homeostasis are poorly understood. Hence, this study determined changes in gene expression due to the loss of ZIP12 in Neuro-2a neuroblastoma cells. Methods: We used RNA-sequencing to uncover differentially expressed genes between cells transfected with a control short hairpin RNA (shRNA) and cells transfected with a shRNA targeting the ZIP12 mRNA sequence. Cells were transfected with NeuroMag (Oz Biosciences) ( n = 6) in 6-well plates and differentiated with all-trans retinoic acid in reduced serum DMEM media for 48 hours. RNA libraries were prepared from total RNA (RNA integrity number >8.0) using the Illumina TruSeq Stranded mRNA Sample Preparation kit. Single-end 75 bp reads were generated on an Illumina NextSeq 500 sequencer. A transcriptome analysis pipeline including Trimmomatic, HISAT2, featureCounts, and DESeq2 was used to identify differentially expressed genes. The cutoff for differential expression was set at log2 fold change of 0.584962, corresponding to a 0.5x increase or decrease in expression relative to control. Results: 25 genes were found which met this cutoff, and all 25 genes had a false discovery rate (FDR) less than 1.0 × 10–9. Using Gene Set Enrichment Analysis (GSEA), we determined that differentially expressed genes (both upregulated and downregulated) were enriched for mitochondria-related function. These mitochondria-related genes include alcohol dehydrogenase-5, peroxiredoxin-3, and galectin-3, and translocase of inner mitochondrial membrane 8 homolog A, and these genes were more likely to be upregulated. Manual identification of genes important for neuronal differentiation in downregulated genes included dopamine beta hydroxylase, astrotactin-2, neural zinc finger-3, neuron specific gene family member-2, inhibitor of DNA binding-2, and inhibitor of DNA binding-3. Conclusions: These findings indicate that changes in the transcriptome induced by loss of ZIP12 function may contribute impairments in neuronal function and reflect altered mitochondrial function. Funding Sources: Oklahoma Center for the Advancement of Science & Technology; Oklahoma Agricultural Experiment Station. The RNA sequencing core is supported by grants from the National Science Foundation.